Effects of movement behaviors on preschoolers’ cognition: a systematic review of randomized controlled trials - Catalina Pacheco; Victoria Culkin; Amelia Putkaradze; Nan Zeng (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Movement behaviors, including physical activity (PA), sedentary behavior (SB), and sleep, are fundamental to early childhood development. These behaviors interact dynamically within a 24-hour period, creating a complex balance that influences not only physical health but also cognitive and emotional well-being in young children. While the physical health benefits of movement behaviors are well-documented, systematic evaluations of how interventions targeting these behaviors affect cognitive development in preschool-aged children remain limited. Methods This review was guided through PRISMA 2020 guidelines. We conducted a systematic review of randomized controlled trials (RCTs) to evaluate the impact of interventions targeting PA, SB, and sleep on cognitive outcomes in preschool-aged children. A comprehensive search was performed across five databases: PubMed, PsycInfo, Web of Science, Embase, and CINAHL, covering studies published between January 2000 and December 2023. Eligible studies were those that focused on at least one movement behavior, had a minimum intervention duration of four weeks, and assessed cognitive development as a primary outcome. The cognitive outcomes evaluated included executive function, attention, memory, and other key domains critical to early childhood development, such as language, processing speed, and social cognition. Results Twenty-two RCTs (14 individual, 8 cluster) met the inclusion criteria. Of these, 21 studies focused on PA, while only one targeted SB, and none specifically addressed sleep or combined movement behaviors. PA interventions, particularly those involving cognitively engaging activities, significantly improved cognitive domains such as executive function, inhibition, and attention, with effect sizes ranging from moderate to large (Cohen’s d > 0.5). The SB-focused study did not report significant cognitive improvements. A clear gap exists in understanding the effects of sleep and multi-behavior interventions on cognitive outcomes. Conclusions Cognitively engaging PA interventions demonstrated the largest effects, while motor skill-focused and general PA programs produced moderate to smaller gains. Evidence on SB and sleep interventions remains limited, with no studies exploring the combined effects of these three movement behaviors. Future research should focus on integrated interventions that address PA, SB, and sleep to achieve a more comprehensive understanding of their collective impact on cognitive development in early childhood. Trial registration This study was registered with PROSPERO under the registration number CRD42023479156.